2018
DOI: 10.1002/cjas.1521
|View full text |Cite
|
Sign up to set email alerts
|

Independent Directors, Business Risk, and the Informativeness of Accounting Earnings for Debt Contracting

Abstract: Using a sample of new bank loans, we investigate the impact of business risk on the usefulness of operating income after controlling for the proportion of independent directors. Consistent with the literature, our initial analyses reveal that the presence of independent directors on a board reduces the interest rate directly and indirectly through an increase in the usefulness of operating income. However, we further provide evidence that the indirect benefit of a high proportion of independent directors is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
(129 reference statements)
1
4
0
Order By: Relevance
“…Those results are rational and explained by the agency theory and resource dependence theory because the decision-making will be more reliable whenever there is a less personal interest which is achieved by the board's independence. The results are consistent with different previous studies such as Al-ahdal et al (2020), Naciti (2019), Uribe-Bohorquez et al (2018), and the Chu, Mathieu, and Mbagwu (2019). The second hypothesis stated that the board size has a significant negative relationship with the firm performance in listed companies in Jordan.…”
Section: Results Discussionsupporting
confidence: 92%
“…Those results are rational and explained by the agency theory and resource dependence theory because the decision-making will be more reliable whenever there is a less personal interest which is achieved by the board's independence. The results are consistent with different previous studies such as Al-ahdal et al (2020), Naciti (2019), Uribe-Bohorquez et al (2018), and the Chu, Mathieu, and Mbagwu (2019). The second hypothesis stated that the board size has a significant negative relationship with the firm performance in listed companies in Jordan.…”
Section: Results Discussionsupporting
confidence: 92%
“…So, the more independent directors connected to politics in the company, the better they are at managing finances, especially in obtaining loans with low interest rates. Therefore, companies need to present independent directors to reduce business risk (Chu et al 2019). When credit conditions are strengthened, independent directors reduce the cost of debt (Bradley and Chen 2015).…”
Section: Ols Regression Resultsmentioning
confidence: 99%
“…In addition to independent commissioners, independent directors also have a very important role in the sustainability of the company because the benefits of the presence of an independent director in the company will reduce the company's business risk (Chu et al 2019). The research of Bradley and Chen (2015) found that the company's independent directors can reduce the cost of debt if credit conditions are strengthened, and with a higher percentage of busy independent directors, the company's cost of debt will decrease (Chakravarty and Rutherford 2017).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The presence of independent directors therefore reduces the propensity to take business risk. In a study on banks, Chu et al (2019) have also established that the benefit of increasing the proportion of independent directors is reduced when we account for business risk.…”
Section: Resultsmentioning
confidence: 99%